2015
DOI: 10.1128/aac.04229-14
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinins, New Miconazole Potentiators Resulting in Increased Activity against Candida albicans Biofilms

Abstract: cMucosal biofilm-related fungal infections are very common, and the incidence of recurrent oral and vulvovaginal candidiasis is significant. As resistance to azoles (the preferred treatment) is occurring, we aimed at identifying compounds that increase the activity of miconazole against Candida albicans biofilms. We screened 1,600 compounds of a drug-repositioning library in combination with a subinhibitory concentration of miconazole. Synergy between the best identified potentiators and miconazole was charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 40 publications
(46 reference statements)
4
60
2
Order By: Relevance
“…They found that artemisinin could inhibit the growth of brine shrimp even at the lowest tested concentration (0Á09 mg ml À1 ), and the brine shrimps were all dead within 1 h of incubation, indicating the high toxicity level of artemisinin against the growth of brine shrimps. In addition, a synergistic effect could not be observed between artesunate and FLC, but artesunate could increase the activity of miconazole against C. albicans biofilms (De Cremer et al 2015).…”
Section: Artemisininmentioning
confidence: 88%
See 1 more Smart Citation
“…They found that artemisinin could inhibit the growth of brine shrimp even at the lowest tested concentration (0Á09 mg ml À1 ), and the brine shrimps were all dead within 1 h of incubation, indicating the high toxicity level of artemisinin against the growth of brine shrimps. In addition, a synergistic effect could not be observed between artesunate and FLC, but artesunate could increase the activity of miconazole against C. albicans biofilms (De Cremer et al 2015).…”
Section: Artemisininmentioning
confidence: 88%
“…In addition, a synergistic effect could not be observed between artesunate and FLC, but artesunate could increase the activity of miconazole against C. albicans biofilms (De Cremer et al . ).…”
Section: The Antifungal Activity Of Traditional Chinese Medicinementioning
confidence: 97%
“…De Cremer and colleagues (2015) found that miconazole and artemisinins combination have the potential to treat infection caused by biofilm formation of one strain of C. albicans. Artemisinins are antimalarial drugs that were found to act synergistically with miconazole because of dihydroartemisinin, a structural homologue of artesunate, a semisynthetic derivative of artemisinin, and its ability to increase the capability of miconazole against biofilms of C. albicans (De Cremer et al, 2015). Furthermore, another study conducted by De Cremer and colleagues (2016) also showed that combination of miconazole (125µM) to antimycin A (25µM) exhibited high superoxide induction, which is significant to fungicidal compounds and their production of ROS to increase susceptibility of miconazole to biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Artemisinins are currently used for treatment of malaria [88], as is chloroquine. These data point to the potential of combination therapy consisting of azoles and antimalarial compounds to treat C. albicans biofilm-related infections [87].…”
Section: Antimicrobial Compoundsmentioning
confidence: 98%
“…De Cremer and co-workers screened a repositioning compound library in the search for miconazole potentiating molecules to treat mature C. albicans biofilms [87]. After screening the Pharmakon 1600 repositioning library, three components exhibited synergy with miconazole: hexachlorophene, pyrvinium pamoate and artesunate.…”
Section: Antimicrobial Compoundsmentioning
confidence: 98%